'Planetary' silver nanoparticles originating from a magnetron sputter plasma. (31st December 2018) - Marom, Sarita; Plesser, Michael; Modi, Ritika; Manini, Nicola; Di Vece, Marcel
Abstract: In a gas aggregation cluster source, nanoparticles are formed by aggregation of single atoms to particles as well as by agglomeration of smaller particles to form larger particles. Because the small particles are often electrically charged, it is possible that particles are mutually attracted or repelled by electric forces. In this work we report the observation of bound multi-nanoparticle systems which are the result of the electrical and centrifugal forces acting on nanoparticles in a magnetron sputtering cluster source. Transmission electron microscopy analysis of the deposited 'planetary' nanoparticle systems exhibits characteristic inter-particle distances and sizes, consistent with different charge states of the particles. Simulations confirm the presence of metastable bound nanoparticle systems up to at least 7/8 satellites. The discovery of such 'planetary' nanoparticle systems inside a cluster source opens up possibilities for more research into their properties and how they can be further controlled and explored.